Pengaruh Model Pembelajaran Missouri Mathematic Project (MMP) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP - Marini Mansyur; Khaerani Khaerani (Program Studi Pendidikan Matematika FKIP Universitas Muslim Maros, 2020)
This research is an experimental research that aims to determine and measure the effect of applying the Missouri Mathematic Project (MMP) learning model to students' mathematical problem solving abilities. This type of research is quantitative research with one group pretest-posttest design. The population in this study were VII grade students of SMP Negeri 4 Bantimurung with 33 random samples taken in one experimental class. Data collection uses tests of students' mathematical problem solving abilities that have been validated by experts. The data of this study were analyzed descriptively and inferentially by the normality test as a test of the prerequisite for analysis. The results of data analysis showed that the average pre-test was 42.09 while the post-test average was 83.73. The average gain normalized score is 0.72 in the high category and is normally distributed for mathematical problem solving ability data. Based on the t-test it can be concluded that there is a significant increase that affects students' mathematical problem solving abilities by applying the Missouri Mathematic project (MMP) learning model.